PENGUATAN WAWASAN KEBANGSAAN SEBAGAI UPAYA PENCEGAHAN PAHAM RADIKALISME DAN INTOLERANSI DI KALANGAN PELAJAR SEKOLAH MENENGAH ATAS NEGERI 3 SALATIGA KOTAMADIA SALATIGA - Iriyanto Widisuseno; Sri Sudarsih (Harmoni: Jurnal Pengabdian Kepada Masyarakat, 2019)
Community service is focused on strengthening the national outlook for students of Salatiga State High School 3. Students are part of the younger generation who will continue the journey of the nation in the future. At the age level of the younger generation, the development of his personality is still unstable. Need to foster and strengthen the identity and character of young students. Through socialization and simulation and understanding of national insights, can broaden views and increase the intensity of appreciation and practice of national values. The goal is that students get a strong grip on the nationality value system so that it is not easily swayed by the western value system which is currently controlling all aspects of human life. The results of this community service show that efforts to strengthen the national outlook appear in the simulation process to be able to foster new awareness and experience about the pillars of national life. The context of the formation is the responsibility of all parties and at the formal level the responsibility of the educational institution.Keywords: Strengthening, nationalism insight, radicalism, intolerance, young generation.